Manufacturing method for recycled titanium dioxide

By treating titanium oxide with superheated steam and subsequent acid washing, the method addresses the issue of sintering and particle enlargement, resulting in high-quality recycled titanium oxide with improved color tone and hiding rate for use in white pigments.

JP7620150B1Active Publication Date: 2025-01-22TAYCA CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024090681
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-11-30
Filing Date
2024-06-04
Publication Date
2025-01-22
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

Existing methods for recycling titanium oxide result in sintering and enlargement of titanium oxide particles due to reaction heat, leading to reduced light scattering and hiding rate, which affects the quality and whiteness of the recycled product.

Method used

Treating a resin composition containing titanium oxide with superheated steam at a specific temperature range, followed by acid washing and pulverization, to control particle size and reduce transition metal impurities, thereby maintaining a good powder color tone and high hiding rate.

Benefits of technology

The method produces recycled titanium oxide with a controlled primary particle size, low transition metal content, and excellent paint color tone, suitable for use as a high-quality white pigment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620150000001
    Figure 0007620150000001
  • Figure 0007620150000002
    Figure 0007620150000002
  • Figure 0007620150000003
    Figure 0007620150000003
Patent Text Reader

Abstract

The present invention provides a method for producing recycled titanium oxide, which can obtain recycled titanium oxide from a resin composition containing titanium oxide, which has a good powder color tone, a primary particle size within a certain range, a low content of transition metal impurities, a good paint color tone, and a high hiding rate. The present invention relates to a method for producing recycled titanium oxide, which comprises treating a resin composition containing titanium oxide with superheated steam at 550 to 1000°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing recycled titanium oxide by treating a resin composition containing titanium oxide, and to a recycled titanium oxide obtained thereby. [Background technology]

[0002] In recent years, environmental and waste problems have led to a worldwide demand for the recovery and recycling of products consumed in the market. Titanium oxide is used in many products as a white pigment, and so attempts have been made to recover the titanium oxide and recycle it as recycled titanium oxide.

[0003] For example, Patent Document 1 describes a method for producing a recycled titanium dioxide pigment for ink, which includes step 1 of preparing raw materials for the recycled titanium dioxide pigment for ink, and step 2 of calcining the raw materials at a temperature of 400°C to 800°C and preparing a recycled titanium dioxide pigment for ink from the resulting calcined product, the raw materials in step 1 being waste plastic film prints containing titanium dioxide pigment, the plastic film prints being a plastic film substrate having an ink coating formed on at least one side thereof, the ink coating having a white ink layer formed with a white ink containing a white pigment made of titanium dioxide and a colored ink layer formed with a colored ink containing a colored pigment other than the white ink, the mass ratio of titanium dioxide to the solid content other than titanium dioxide in the white ink layer being 0.1 to 6, and the thickness of the plastic film substrate being 10 to 60 μm.

[0004] Patent Document 2 describes a method for recovering titanium oxide from titanium oxide-containing plastics, which comprises heating the titanium oxide-containing plastic in an oxygen-containing atmosphere at 800 to 1000°C to combust organic components contained in the titanium oxide-containing plastic and converting the titanium oxide components contained in the titanium oxide-containing plastic to anatase type, and reusing the resulting combustion residue containing anatase type titanium oxide as a raw material for manufacturing titanium oxide using a sulfuric acid method to recover titanium oxide.

[0005] Patent Document 3 describes a method for recovering titanium dioxide, which comprises crushing waste polyvinyl chloride resin containing calcium carbonate and titanium dioxide, heating and dehydrochlorinating the resulting residue, washing the residue with an aqueous liquid, and then burning and treating the residue, and recovering the resulting residue as titanium dioxide. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 7232375 [Patent Document 2] JP 2001-253713 A [Patent Document 3] Patent No. 4628721 Summary of the Invention [Problem to be solved by the invention]

[0007] These Patent Documents 1 to 3 aim to recover titanium oxide, but all of them are methods for recovering titanium oxide after calcination in an air atmosphere. The inventors have found that in the method of calcination in an air atmosphere, even if a constant temperature is set, the reaction heat is generated due to the combustion reaction, and there is a risk that titanium oxide will be sintered and enlarged. Enlarged titanium oxide has reduced light scattering, and reduced hiding power and whiteness, so there is a quality issue when it is recycled as recycled titanium oxide.

[0008] The present invention has been made in order to solve the above-mentioned problems, and has an object to provide a method for producing recycled titanium oxide which can obtain, from a resin composition containing titanium oxide, recycled titanium oxide which has a good powder color tone, a primary particle size within a certain range, a low content of transition metal impurities, a good paint color tone, and a high hiding rate. [Means for solving the problem]

[0009] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by a method for producing recycled titanium oxide, in which a resin composition containing titanium oxide is treated with superheated steam within a certain temperature range, and have completed the present invention.

[0010] That is, the present invention provides [1] A method for producing recycled titanium oxide, comprising treating a resin composition containing titanium oxide with superheated steam at 550 to 1,000°C; [2] The method for producing recycled titanium oxide according to [1], which comprises washing with an acid before or after the superheated steam treatment; [3] The method for producing recycled titanium oxide according to [1] or [2], which comprises pulverizing the titanium oxide after the superheated steam treatment; [4] Recycled titanium oxide obtained by recycling a resin composition containing titanium oxide, the recycled titanium oxide having a powder color tone L value of 50 or more and a D50 measured by TEM of 0.18 μm or more and 0.31 μm or less; [5] Recycled titanium dioxide according to [4], having a total acid-insoluble transition metal content of 1.0 mass% or less; [6] The recycled titanium oxide according to [4] or [5], wherein the reflectance of powder pellets obtained by molding the recycled titanium oxide into pellets at a wavelength of 420 nm is 85% or more; [7] The recycled titanium dioxide according to any one of [4] to [6], wherein the L value of the paint color tone in the Lab color system of a coating film containing the recycled titanium dioxide and boiled linseed oil is 85 or more and the b value is 4.3 or less; [8] A recycled titanium dioxide according to any one of [4] to [7], in which a coating film containing the recycled titanium dioxide and boiled linseed oil has an L value of 93.5 or more in the Lab color system, and a hiding rate of 99.5% or more in a hiding rate test; [9] Recycled titanium oxide obtained by recycling a resin composition containing titanium oxide, the recycled titanium oxide having a powder color tone L value of 50 or more and a D10 measured by TEM of 0.29 μm or less;

[10] Recycled titanium oxide obtained by recycling a resin composition containing titanium oxide, the recycled titanium oxide having a powder color tone L value of 50 or more and a D90 measured by TEM of 0.71 μm or less;

[11] Recycled titanium oxide obtained by recycling a resin composition containing titanium oxide, the L value of the powder color tone being 50 or more, and the difference between D90 and D10 measured by TEM being 0.46 μm or less;

[12] [4]-

[11] Ink containing recycled titanium dioxide; Regarding. Effect of the Invention

[0011] According to the manufacturing method of the present invention, it is possible to obtain recycled titanium oxide from a resin composition containing titanium oxide, which has a good powder color tone, a primary particle size within a certain range, a low content of transition metal impurities, a good paint color tone, and a high hiding power. The recycled titanium oxide thus obtained is of excellent quality and is suitable for use as a white pigment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The method for producing recycled titanium oxide of the present invention is characterized in that a resin composition containing titanium oxide is treated with superheated steam at 550 to 1000°C (sometimes referred to as a "superheated steam treatment step"). The present inventors have focused on the fact that the chemical reaction between a hydrocarbon such as CH4 and superheated steam is an endothermic reaction, and have conducted extensive research. As a result, it has become clear that by treating a resin composition containing titanium oxide with superheated steam at a certain temperature range, titanium oxide can be prevented from sintering and becoming enlarged, and the powder color tone becomes good. As can be seen from a comparison between the examples and comparative examples described below, in the comparative example in which the reaction was carried out in air, even if the reaction temperature was set to a certain temperature, reaction heat was generated because it was a combustion reaction, and as a result, it was confirmed that the primary particle diameter (D50) of the obtained titanium oxide reached a certain value or more, and the titanium oxide was enlarged. In addition, in the comparative example in which the reaction was carried out in an inert atmosphere, the powder color tone of the obtained titanium oxide was not good. In contrast, in the examples in which a resin composition containing titanium oxide was treated with superheated steam within a certain temperature range, recycled titanium oxide was obtained that had a good powder color tone, a primary particle diameter (D50) within a certain range, a low content of transition metal impurities, a good paint color tone, and a high hiding rate. Therefore, it is understood that there is great significance in adopting the method for producing recycled titanium oxide of the present invention. Note that, if a resin composition containing titanium oxide is treated with superheated steam within a certain temperature range, a reaction in an inert atmosphere may be combined with the superheated steam treatment.

[0013] The type of resin constituting the resin composition is not particularly limited, but examples include polyolefins such as polyethylene, polypropylene, and ethylene-vinyl acetate copolymers; polyamides; polyesters; polystyrene; polyurethanes; polyvinyl chloride; polycarbonates; acrylic resins; epoxy resins; and silicone resins.

[0014] In the present invention, the reaction temperature of the superheated steam treatment step is 550 to 1000°C. If the reaction temperature of the superheated steam treatment step is less than 550°C, the reaction does not proceed sufficiently, and titanium oxide having a good powder color tone cannot be obtained. The reaction temperature of the superheated steam treatment step is preferably 580°C or higher, more preferably 600°C or higher, even more preferably 680°C or higher, particularly preferably 750°C or higher, and most preferably 780°C or higher. On the other hand, if the reaction temperature of the superheated steam treatment step exceeds 1000°C, there is a risk of sintering and enlargement of titanium oxide. The reaction temperature of the superheated steam treatment step is preferably 980°C or lower, more preferably 920°C or lower, and even more preferably 820°C or lower.

[0015] In the present invention, the reaction time of the superheated steam treatment step is not particularly limited. The reaction time in the present invention refers to the time from the start of the superheated steam treatment from a state in which the reaction temperature of the above-mentioned superheated steam treatment step is maintained until the end of the reaction. The reaction time is preferably 0.1 to 10 hours, more preferably 0.2 to 6 hours, and even more preferably 0.5 to 4 hours. In addition, the means for maintaining the reaction temperature of the above-mentioned superheated steam treatment step is not particularly limited, and a method of raising the temperature to a desired reaction temperature by superheated steam is preferably adopted. That is, a preferred embodiment of the present invention is to raise the temperature to a desired reaction temperature and perform the superheated steam treatment while maintaining the reaction temperature. The time until the temperature is raised is not particularly limited, and is preferably 0.1 to 4 hours, more preferably 0.2 to 3 hours, and even more preferably 0.5 to 2 hours.

[0016] In the present invention, washing with an acid (sometimes referred to as an "acid washing step") before or after the superheated steam treatment is a preferred embodiment. This allows the metal oxides and metal salts remaining after the superheated steam treatment to be removed with an acid, making it possible to obtain recycled titanium oxide with high purity and good powder color tone. Among these, washing with an acid after the superheated steam treatment is a more preferred embodiment. The acid used is not particularly limited, and may be a water-soluble inorganic acid or organic acid. As the inorganic acid, at least one selected from the group consisting of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, hydrofluoric acid, etc. is preferably used, and as the organic acid, at least one selected from the group consisting of acetic acid, oxalic acid, citric acid, etc. is preferably used, and among these, at least one acid selected from the group consisting of sulfuric acid, hydrochloric acid, and nitric acid is more preferably used. As a method for washing with an acid, a method in which an aqueous solution of the above-mentioned acid is added to the titanium oxide after the superheated steam treatment and mixed is preferably used. After the acid washing step, a filtration and water washing step is preferably performed. As the filtration and water washing step, a known method is used. In a preferred embodiment, a drying step is carried out after the filtration and washing step. The drying temperature is preferably 100 to 130°C, and more preferably 105 to 115°C.

[0017] In the present invention, pulverization (sometimes referred to as a "pulverization step") after the superheated steam treatment is a preferred embodiment. As a pulverization method, pulverization is preferably performed using a known pulverizer or the like. The pulverizer is not particularly limited, and an ultracentrifugal pulverizer, ball mill, air flow mill, hammer mill, Raikai mill, or the like can be used. By this pulverization, recycled titanium oxide having a primary particle size (D50) within a certain range can be obtained. The pulverization is preferably performed as the final step for obtaining recycled titanium oxide. Therefore, it is a preferred embodiment to perform the acid washing step before the pulverization step.

[0018] The recycled titanium oxide obtained by the present invention has a powder color L value of 50 or more, and a TEM D50 of 0.18 μm or more and 0.31 μm or less. Since the powder color L value is a certain value or more and the TEM D50 is within a certain range, it can be recycled as a high-quality recycled titanium oxide. The powder color L value is preferably 50 or more, more preferably 70 or more, even more preferably 85 or more, particularly preferably 92 or more, and most preferably 95 or more. The powder color L value indicates the L value in the Lab color system measured using a colorimeter.

[0019] Furthermore, the D50 by TEM is preferably 0.18 μm or more, more preferably 0.21 μm or more, even more preferably 0.22 μm or more, and most preferably 0.23 μm or more. On the other hand, the D50 by TEM is preferably 0.31 μm or less, preferably 0.30 μm or less, and even more preferably 0.29 μm or less. The D50 by TEM means the particle diameter (median diameter) at 50% of cumulative in the volume-based particle size distribution obtained by photographing a certain number of primary particles of titanium oxide using a transmission electron microscope and measuring the particle size distribution using image analysis type particle size distribution measurement software.

[0020] In addition, the recycled titanium oxide obtained by the present invention has a powder color L value of 50 or more and a TEM D10 of 0.29 μm or less. Since the powder color L value is at least a certain level and the TEM D10 is within a certain range, it can be recycled as high-quality recycled titanium oxide.

[0021] D10 by TEM is preferably 0.29 μm or less, more preferably 0.27 μm or less, even more preferably 0.25 μm or less, and most preferably 0.24 μm or less. D10 by TEM is preferably 0.12 μm or more, more preferably 0.16 μm or more, and even more preferably 0.20 μm or more. D10 by TEM means the particle size at 10% of the cumulative volumetric particle size distribution obtained by photographing a certain number of primary particles of titanium oxide using a transmission electron microscope and measuring the particle size distribution using image analysis type particle size distribution measurement software.

[0022] In addition, the recycled titanium oxide obtained by the present invention has a powder color L value of 50 or more and a TEM D90 of 0.71 μm or less. Since the powder color L value is at least a certain level and the TEM D90 is within a certain range, it can be recycled as high-quality recycled titanium oxide.

[0023] D90 by TEM is preferably 0.71 μm or less, more preferably 0.68 μm or less, even more preferably 0.65 μm or less, and most preferably 0.64 μm or less. D90 by TEM is preferably 0.23 μm or more, more preferably 0.27 μm or more, and even more preferably 0.32 μm or more. D90 by TEM means the particle size at 90% of the cumulative volumetric particle size distribution obtained by photographing a certain number of primary particles of titanium oxide using a transmission electron microscope and measuring the particle size distribution using image analysis particle size distribution measurement software.

[0024] Furthermore, the recycled titanium oxide obtained by the present invention has a powder color L value of 50 or more, and the difference between D90 and D10 measured by TEM (sometimes referred to as "D90-D10") is 0.46 μm or less. Since the powder color L value is at least a certain level, and the difference between D90 and D10 measured by TEM is within a certain range, it can be recycled as high-quality recycled titanium oxide.

[0025] The difference between D90 and D10 by TEM is preferably 0.46 μm or less, more preferably 0.41 μm or less, and even more preferably 0.36 μm or less. The difference between D90 and D10 by TEM is preferably 0.06 μm or more.

[0026] The recycled titanium oxide obtained by the present invention preferably has a total acid-insoluble transition metal content of 1.0% by mass or less. The total acid-insoluble transition metal content refers to the total transition metal content remaining after the acid washing process, and the transition metal is derived from the metal oxide, metal salt, etc. contained in the resin composition. Specifically, it refers to the total content of transition metals derived from CuO and Fe2O3. When the transition metal content exceeds 1.0% by mass, the whiteness decreases, and there is a risk that the quality is insufficient for recycling. The transition metal content is more preferably 0.8% by mass or less, further preferably 0.6% by mass or less, particularly preferably 0.4% by mass or less, and most preferably 0.3% by mass or less. On the other hand, the transition metal content is 0% by mass or more, and may be 0.005% by mass or more, 0.01% by mass or more, or 0.05% by mass or more.

[0027] The powder pellets obtained by molding the recycled titanium oxide obtained by the present invention into pellets preferably have a reflectance at a wavelength of 420 nm of 85% or more. When the reflectance is at a certain level or higher, it is possible to recycle the titanium oxide into high-quality recycled titanium oxide. The reflectance is more preferably 87% or more, even more preferably 88% or more, and particularly preferably 94% or more. The reflectance is usually 100% or less.

[0028] The recycled titanium oxide obtained by the present invention preferably has a paint color tone L value of 85 or more and a b value of 4.3 or less in the Lab color system of a coating film containing the recycled titanium oxide and boiled linseed oil. If the L value of the paint color tone is less than 85, the quality may be insufficient for recycling, and is more preferably 88 or more, more preferably 90 or more, even more preferably 92 or more, particularly preferably 93.5 or more, and most preferably 94 or more. The L value of the paint color tone is usually 99 or less. If the b value of the paint color tone exceeds 4.3, the quality may be insufficient for recycling, and is more preferably 4.2 or less, even more preferably 4.1 or less, particularly preferably 4.0 or less, and most preferably 3.9 or less. The L value and b value of the paint color tone respectively indicate the L value and b value in the Lab color system measured using a colorimeter.

[0029] In addition, the recycled titanium oxide obtained by the present invention preferably has a hiding rate of 99.5% or more in a coating film containing the recycled titanium oxide and boiled linseed oil. If the hiding rate is less than 99.5%, the quality may be insufficient when used as a paint, and it is more preferably 99.6% or more, even more preferably 99.7% or more, and particularly preferably 99.8% or more. The hiding rate is usually 100% or less. The hiding rate is calculated according to the following formula by measuring the L value in the Lab color system for coating films painted on a white board and a black board using a colorimeter in accordance with JISK5600 (general test method for paints).

number

[0030] The recycled titanium oxide obtained by the present invention has a good powder color tone, a primary particle size within a certain range, a low content of transition metal impurities, a good paint color tone, and a high hiding rate. Therefore, it is suitable for use as a white pigment in paints, inks, paper, molding resin compounds, etc. Among them, the ink containing the recycled titanium oxide obtained by the present invention is a more suitable embodiment. The recycled titanium oxide obtained by the present invention is obtained by recovering it from a resin composition containing titanium oxide. Therefore, the method of recovering recycled titanium oxide from a resin composition containing titanium oxide is a suitable embodiment, and the resin composition containing recycled titanium oxide obtained by the present invention is also a suitable embodiment. EXAMPLES

[0031] The present invention will now be described in more detail with reference to examples.

[0032] Preparation example 1 90g of titanium oxide, 3.3g of phthalocyanine blue (0.5% by mass of CuO relative to 100% by mass of titanium oxide), 100g of polyurethane resin, and 73.3g of solvent were mixed together, placed in a 400mL mayonnaise bottle together with 180g of 1.5mm glass beads, and dispersed for 1 hour using a paint conditioner (manufactured by Red Devil) to produce an ink. The following materials were used for the mixture. Titanium oxide: "Titanix JR-707" (manufactured by Teika Co., Ltd.) Phthalocyanine blue: "Phthalocyanine blue" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Polyurethane resin: "Sanprene IB-422" (manufactured by Sanyo Chemical Industries, Ltd.) Solvent: A mixed solvent of methyl ethyl ketone, isopropyl alcohol, and toluene (1 / 1 / 1 by weight) This operation was repeated several times to prepare a total of 13 kg of ink. The resulting 13 kg of ink was spread thinly and dried at 120° C. for 12 hours to obtain 6 kg of a titanium oxide resin composition containing 0.5% by mass of CuO.

[0033] Example 2 90g of titanium oxide, 6.6g of phthalocyanine blue (1.0% by mass of CuO relative to 100% by mass of titanium oxide), 100g of polyurethane resin, and 73.3g of solvent were mixed together, placed in a 400mL mayonnaise bottle together with 180g of 1.5mm glass beads, and dispersed for 1 hour using a paint conditioner (manufactured by Red Devil) to produce an ink. The following materials were used for the mixture. Titanium oxide: "Titanix JR-707" (manufactured by Teika Co., Ltd.) Phthalocyanine blue: "Phthalocyanine blue" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Polyurethane resin: "Sanprene IB-422" (manufactured by Sanyo Chemical Industries, Ltd.) Solvent: A mixed solvent of methyl ethyl ketone, isopropyl alcohol, and toluene (1 / 1 / 1 by weight) This operation was repeated several times to prepare a total of 13 kg of ink. The resulting 13 kg of ink was spread thinly and dried at 120° C. for 12 hours to obtain 6 kg of a titanium oxide resin composition containing 1.0% by mass of CuO.

[0034] Preparation example 3 90g of titanium oxide, 3.3g of phthalocyanine blue (0.5% by mass in CuO conversion relative to 100% by mass of titanium oxide), 0.45g of iron (III) oxide (0.5% by mass in Fe2O3 conversion relative to 100% by mass of titanium oxide), 100g of polyurethane resin, and 73.3g of solvent were mixed in a compounding ratio, placed in a 400mL mayonnaise bottle together with 180g of 1.5mm glass beads, and dispersed for 1 hour using a paint conditioner (manufactured by Red Devil) to prepare the ink. The following materials were used for the compounding materials. Titanium oxide: "Titanix JR-707" (manufactured by Teika Co., Ltd.) Phthalocyanine blue: "Phthalocyanine blue" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Iron(III) oxide: "Iron(III) oxide" (FUJIFILM Wako Pure Chemical Industries, Ltd.) Polyurethane resin: "Sanprene IB-422" (manufactured by Sanyo Chemical Industries, Ltd.) Solvent: A mixed solvent of methyl ethyl ketone, isopropyl alcohol, and toluene (1 / 1 / 1 by weight) This operation was repeated several times to prepare a total of 13 kg of ink. The resulting ink (13 kg) was spread thinly and dried at 120° C. for 12 hours to obtain 6 kg of a titanium oxide resin composition containing 0.5% by mass of CuO and 0.5% by mass of Fe2O3.

[0035] Preparation Example 4 90g of titanium oxide, 3.3g of phthalocyanine blue (0.5% by mass of CuO relative to 100% by mass of titanium oxide), 100g of polyurethane resin, and 73.3g of solvent were mixed together, placed in a 400mL mayonnaise bottle together with 180g of 1.5mm glass beads, and dispersed for 1 hour using a paint conditioner (manufactured by Red Devil) to produce an ink. The following materials were used for the mixture. Titanium oxide: "Titanix JR-809" (manufactured by Teika Co., Ltd.) Phthalocyanine blue: "Phthalocyanine blue" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Polyurethane resin: "Sanprene IB-422" (manufactured by Sanyo Chemical Industries, Ltd.) Solvent: A mixed solvent of methyl ethyl ketone, isopropyl alcohol, and toluene (1 / 1 / 1 by weight) This operation was repeated several times to prepare a total of 13 kg of ink. The resulting ink (13 kg) was spread thinly and dried at 120° C. for 12 hours to obtain 6 kg of a titanium oxide resin composition containing 0.5% by mass of CuO.

[0036] Preparation example 5 6 kg of the resin composition prepared in Preparation Example 1 was cut into 1 cm cubes and immersed in 30 kg of 1% by mass sodium hydroxide solution for 1 hour. 100 L of water was added to 20 kg of the soaked material (water content 70% by mass), stirred for 30 minutes, and the sample collected by filtration was washed with twice the amount of water. After that, it was dried in a dryer at 110°C for 24 hours to obtain 6 kg of an alkali cleaning resin composition of titanium oxide containing 0.5% by mass of CuO.

[0037] Example 1 1 kg of the resin composition of Preparation Example 1 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (600°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 600°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0038] Example 2 1 kg of the resin composition of Preparation Example 5 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (700°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 700°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0039] Example 3 1 kg of the resin composition of Preparation Example 1 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (800°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0040] Example 4 1 kg of the resin composition of Preparation Example 1 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (900°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 900°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0041] Example 5 1 kg of the resin composition of Preparation Example 1 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (1000°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 1000°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0042] Example 6 1 kg of the resin composition of Preparation Example 1 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (550°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 550°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0043] Example 7 1 kg of the resin composition of Preparation Example 1 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (580°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 580°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0044] Example 8 1 kg of the resin composition of Preparation Example 1 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0045] Example 9 1 kg of the resin composition of Preparation Example 1 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added while stirring well to make 5 L. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0046] Example 10 1 kg of the resin composition of Preparation Example 5 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0047] Example 11 1 kg of the resin composition of Preparation Example 2 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0048] Example 12 1 kg of the resin composition of Preparation Example 2 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added while stirring well to make 5 L. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0049] Example 13 1 kg of the resin composition of Preparation Example 2 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0050] Example 14 1 kg of the resin composition of Preparation Example 3 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0051] Example 15 1 kg of the resin composition of Preparation Example 3 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added while stirring well to make 5 L. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0052] Example 16 1 kg of the resin composition of Preparation Example 3 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0053] Example 17 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Co., Ltd.), heated from room temperature to 800°C in 1 hour under a nitrogen atmosphere, and held at that temperature for 6 hours to pyrolyze the contents. The pyrolyzed product obtained was then placed in a batch-type superheated steam furnace (product name: manufactured by Takasago Kogyo Co., Ltd.) and heated from room temperature to 150°C in 1 hour, and then heated to 800°C in 1 hour by introducing superheated steam (800°C x 5 kg / hr) into the furnace, and held at that temperature for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0054] Example 18 1 kg of the resin composition of Preparation Example 4 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (800°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0055] Comparative Example 1 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), heated from room temperature to 500°C over 1 hour, and then held at that temperature for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0056] Comparative Example 2 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), and the temperature was raised from room temperature to 600°C over 1 hour, and then the temperature was maintained for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0057] Comparative Example 3 1 kg of the resin composition of Preparation Example 5 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), heated from room temperature to 700°C over 1 hour, and then held at that temperature for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0058] Comparative Example 4 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), and the temperature was raised from room temperature to 800°C over 1 hour, and then the temperature was maintained for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0059] Comparative Example 5 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), heated from room temperature to 900°C over 1 hour, and then held at that temperature for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0060] Comparative Example 6 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), and the temperature was raised from room temperature to 1000°C over 1 hour, and then the temperature was maintained for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0061] Comparative Example 7 1 kg of the resin composition of Preparation Example 1 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (500°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 500°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0062] Comparative Example 8 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0063] Comparative Example 9 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0064] Comparative Example 10 1 kg of the resin composition of Preparation Example 5 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0065] Comparative Example 11 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), heated from room temperature to 800°C in 1 hour under a nitrogen atmosphere, and held at that temperature for 6 hours to pyrolyze the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0066] Comparative Example 12 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), heated from room temperature to 800°C in 1 hour under a nitrogen atmosphere, and held at that temperature for 6 hours to pyrolyze the contents. The pyrolyzed product obtained was then placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), heated from room temperature to 500°C in 1 hour in air, and held at that temperature for 6 hours to fire the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0067] Comparative Example 13 1 kg of the resin composition of Preparation Example 1 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), heated from room temperature to 800°C in 1 hour under a nitrogen atmosphere, and held at that temperature for 6 hours to pyrolyze the contents. The pyrolyzed product obtained was then placed in a small electric furnace KBF828N2 (trade name: manufactured by JTEKT Thermo Systems), heated from room temperature to 800°C in 1 hour in air, and held at that temperature for 6 hours to fire the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0068] Comparative Example 14 1 kg of the resin composition of Preparation Example 4 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), heated from room temperature to 800°C over 1 hour, and then held at that temperature for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0069] Preparation Example 6 120g of titanium oxide, 4.4g of phthalocyanine blue (0.5% by mass of CuO relative to 100% by mass of titanium oxide), 28.8g of alkyd resin, and 28.8g of solvent were mixed together, placed in a 400mL mayonnaise bottle together with 300g of 1.5mm glass beads, and dispersed for 1 hour using a paint conditioner (manufactured by Red Devil). After that, 111.2g of alkyd resin and 60.0g of butylated melamine resin were added to prepare a paint. The following materials were used for the mixture. Titanium oxide: "Titanix JR-600A" (manufactured by Teika Co., Ltd.) Phthalocyanine blue: "Phthalocyanine blue" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Alkyd resin: "Alkidia J-524-A" (DIC) Butylated melamine resin: "Amidia J-820-60" (DIC Corporation) Solvent: Mixture of xylene / n-butanol = 4 / 1 by mass This operation was repeated several times to prepare a total of 18 kg of paint. The resulting 18 kg of paint was spread thinly and dried at 120° C. for 12 hours to obtain 6 kg of a titanium oxide resin composition containing 0.5% by mass of CuO.

[0070] Example 19 1 kg of the resin composition of Preparation Example 6 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (800°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0071] Example 20 1 kg of the resin composition of Preparation Example 6 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added while stirring well to make 5 L. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0072] Example 21 1 kg of the resin composition of Preparation Example 6 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0073] Example 22 1 kg of the resin composition of Preparation Example 6 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0074] Comparative Example 15 1 kg of the resin composition of Preparation Example 6 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), heated from room temperature to 800°C over 1 hour, and then held at that temperature for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0075] Comparative Example 16 1 kg of the resin composition of Preparation Example 6 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0076] Comparative Example 17 1 kg of the resin composition of Preparation Example 6 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0077] Comparative Example 18 1 kg of the resin composition of Preparation Example 6 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0078] Preparation Example 7 120g of titanium oxide, 4.4g of phthalocyanine blue (0.5% by mass of CuO relative to 100% by mass of titanium oxide), 28.8g of alkyd resin, and 28.8g of solvent were mixed together, placed in a 400mL mayonnaise bottle together with 300g of 1.5mm glass beads, and dispersed for 1 hour using a paint conditioner (manufactured by Red Devil). After that, 111.2g of alkyd resin and 60.0g of butylated melamine resin were added to prepare a paint. The following materials were used for the mixture. Titanium oxide: "Titanix JR-805" (manufactured by Teika Co., Ltd.) Phthalocyanine blue: "Phthalocyanine blue" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Alkyd resin: "Alkidia J-524-A" (DIC) Butylated melamine resin: "Amidea J-820-60" (DIC Corporation) Solvent: Mixture of xylene / n-butanol = 4 / 1 by mass This operation was repeated several times to prepare a total of 18 kg of paint. The resulting 18 kg of paint was spread thinly and dried at 120° C. for 12 hours to obtain 6 kg of a titanium oxide resin composition containing 0.5% by mass of CuO.

[0079] Example 23 1 kg of the resin composition of Preparation Example 7 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (800°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0080] Example 24 1 kg of the resin composition of Preparation Example 7 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0081] Example 25 1 kg of the resin composition of Preparation Example 7 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added while stirring well to make 5 L. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0082] Example 26 1 kg of the resin composition of Preparation Example 7 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0083] Comparative Example 19 1 kg of the resin composition of Preparation Example 7 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), heated from room temperature to 800°C over 1 hour, and then held at that temperature for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0084] Comparative Example 20 1 kg of the resin composition of Preparation Example 7 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0085] Comparative Example 21 1 kg of the resin composition of Preparation Example 7 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corporation), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0086] Comparative Example 22 1 kg of the resin composition of Preparation Example 7 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0087] Example 8 90g of titanium oxide, 3.3g of phthalocyanine blue (0.5% by mass of CuO relative to 100% by mass of titanium oxide), 100g of polyurethane resin, and 73.3g of solvent were mixed together, placed in a 400mL mayonnaise bottle together with 180g of 1.5mm glass beads, and dispersed for 1 hour using a paint conditioner (manufactured by Red Devil) to produce an ink. The following materials were used for the mixture. Titanium oxide: "Titanix JR-405" (manufactured by Teika Co., Ltd.) Phthalocyanine blue: "Phthalocyanine blue" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Polyurethane resin: "Sanprene IB-422" (manufactured by Sanyo Chemical Industries, Ltd.) Solvent: A mixed solvent of methyl ethyl ketone, isopropyl alcohol, and toluene (1 / 1 / 1 by weight) This operation was repeated several times to prepare a total of 13 kg of ink. The resulting 13 kg of ink was spread thinly and dried at 120° C. for 12 hours to obtain 6 kg of a titanium oxide resin composition containing 0.5% by mass of CuO.

[0088] Example 27 1 kg of the resin composition of Preparation Example 8 was placed in a batch-type superheated steam furnace (manufactured by Takasago Industrial Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour, and then superheated steam (800°C x 5 kg / hr) was introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour to perform steam pyrolysis of the contents. The obtained powder was pulverized to obtain recycled titanium oxide.

[0089] Example 28 1 kg of the resin composition of Preparation Example 8 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0090] Example 29 1 kg of the resin composition of Preparation Example 8 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added while stirring well to make 5 L. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0091] Example 30 1 kg of the resin composition of Preparation Example 8 was placed in a batch-type superheated steam furnace (manufactured by Takasago Kogyo Co., Ltd.), and the temperature was raised from room temperature to 150°C in 1 hour. Superheated steam (800°C x 5 kg / hr) was then introduced into the furnace to raise the temperature to 800°C in 1 hour, and the temperature was maintained for 1 hour, and the contents were subjected to steam pyrolysis. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0092] Comparative Example 23 1 kg of the resin composition of Preparation Example 8 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems Corp.), heated from room temperature to 800°C over 1 hour, and then held at that temperature for 12 hours to sinter the contents. The resulting powder was pulverized to obtain recycled titanium oxide.

[0093] Comparative Example 24 1 kg of the resin composition of Preparation Example 8 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass sulfuric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0094] Comparative Example 25 1 kg of the resin composition of Preparation Example 8 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass nitric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The sample collected by filtration was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0095] Comparative Example 26 1 kg of the resin composition of Preparation Example 8 was placed in a small electric furnace KBF828N2 (manufactured by JTEKT Thermo Systems), and the temperature was raised from room temperature to 800°C in 1 hour, and then the temperature was maintained for 12 hours to calcinate the contents. 650 mL of 50% by mass hydrochloric acid was added to 500 g of the obtained titanium oxide pigment, and water was added to make 5 L while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The filtered sample was washed with 5 L of water and dried in a dryer at 110°C for 5 hours. The obtained powder was pulverized to obtain recycled titanium oxide.

[0096] Evaluation 1: Powder color evaluation 5 g of the titanium oxide obtained in Examples 1 to 30 and Comparative Examples 1 to 26 was press-molded into pellets at 100 MPa to obtain titanium oxide molded bodies with a diameter of 3 cm and a thickness of 0.3 cm. The powder color tone (L, a, b) of the titanium oxide molded bodies was measured using a colorimeter ZE2000 (manufactured by Nippon Denshoku Industries Co., Ltd.). The obtained results are summarized in Tables 1 and 2.

[0097] Evaluation 2: Evaluation of particle size (D50, D10, D90 by TEM) For the titanium oxides obtained in Examples 1 to 30 and Comparative Examples 1 to 26, 500 or more primary particles of titanium oxide were photographed using a JEM-1230 transmission electron microscope (manufactured by JEOL Ltd.), and the particle size distribution was measured using image analysis particle size distribution measurement software Mac-View (manufactured by Mountec Co., Ltd.), and D50, D10, D90, and the difference between D90 and D10, "D90-D10," were evaluated. The obtained results are summarized in Tables 1 and 2.

[0098] Evaluation 3: Evaluation of the amount of transition metals (CuO, Fe2O3) that are insoluble in acid 32.5 mL of 50% by mass sulfuric acid, 50% by mass hydrochloric acid, or 50% by mass nitric acid was added to 25 g of titanium oxide obtained in Examples 1 to 30 and Comparative Examples 1 to 26, and water was added to make 250 mL while stirring well. The obtained liquid was boiled for 5 minutes while stirring, and then cooled to room temperature. The slurry was filtered, washed with water, and dried to remove the transition metals that dissolve in acid. 5 g of the obtained titanium oxide containing the transition metals that are not soluble in acid was press-molded into a pellet at 100 MPa to obtain a titanium oxide molded body with a diameter of 3 cm and a thickness of 0.3 cm. The elemental composition was measured using a tabletop wavelength dispersive X-ray fluorescence analyzer Supermini (manufactured by Rigaku Corporation), and the amount of transition metals that are not soluble in acid (CuO, Fe2O3) was measured. The obtained results are summarized in Tables 1 and 2.

[0099] Evaluation 4: Evaluation of reflectance (%) at 420 nm by powder pellet molding The titanium oxides obtained in Examples 1 to 30 and Comparative Examples 1 to 26 were press-molded into pellets at 100 MPa to obtain titanium oxide molded bodies having a diameter of 3 cm and a thickness of 0.3 cm. The reflectance curves of the titanium oxide molded bodies were measured in the wavelength range of 300 nm to 700 nm using a spectrophotometer HITACHI U-4100 (manufactured by Hitachi, Ltd.) with a BaSO4 standard tablet as a reference. The reflectance at 420 nm was evaluated from the obtained reflectance curves. The obtained results are summarized in Tables 3 and 4.

[0100] Evaluation 5: Evaluation of paint color tone and hiding rate test (hiding rate) using boiled linseed oil 1.5 mL of boiled linseed oil was added to 1.5 g of titanium oxide obtained in Examples 1 to 30 and Comparative Examples 1 to 26. The obtained sample was dispersed for 15 seconds using a Huber Marler. This dispersion was repeated a total of four times. The obtained dispersion paste was applied to a JIS K5600 paint general test method hiding rate test paper using a 1.5 mil film applicator. The paint color tone on a white board and a black board was measured using a colorimeter ZE2000 (manufactured by Nippon Denshoku Industries Co., Ltd.). The hiding rate was calculated from the following formula. The obtained results are summarized in Tables 3 and 4.

[0101]

number

[0102] [Table 1]

[0103] [Table 2]

[0104] [Table 3]

[0105] [Table 4]

[0106] As shown in Tables 1 to 4, the recycled titanium oxides of Examples 1 to 30, which were obtained by treating a resin composition containing titanium oxide with superheated steam within a certain temperature range, satisfy all of the required qualities for a white pigment of titanium oxide, such as: (1) the L value of the powder color is high and the powder color is good; (2) the particle size (D50 by TEM) is not large and the primary particle size is within a certain range; (3) the content of acid-insoluble transition metals, which are impurities, is low; (4) the L value of the paint color (white board) using boiled linseed oil is high, the b value is low and the paint color is good; and (5) the hiding rate is also high. On the other hand, the recycled titanium oxides of Comparative Examples 1 to 26, which were obtained by heating a resin composition containing titanium oxide in air or an inert atmosphere, or by treating it with superheated steam outside a certain temperature range, do not meet the quality requirements for a white pigment of titanium oxide, for example: (1) the L value of the powder color is low; (2) the particle size (D50 by TEM) is large and the primary particle size is enlarged; (3) the content of acid-insoluble transition metals is high; and (4) the L value of the paint color (white board) obtained using boiled linseed oil is low and the b value is high.

Claims

1. A method for producing recycled titanium oxide, comprising treating a resin composition containing titanium oxide with superheated steam at 550 to 1000°C, The recycled titanium oxide is The L value of the powder color tone is 50 or more, and the D50 measured by TEM is 0.18 μm or more and 0.31 μm or less; The L value of the powder color tone is 50 or more, and the D10 measured by TEM is 0.29 μm or less; The L value of the powder color tone is 50 or more, and the D90 measured by TEM is 0.71 μm or less; or a method for producing recycled titanium oxide, which satisfies either one of the following: the L value of the powder color tone is 50 or more, and the difference between D90 and D10 measured by TEM is 0.46 μm or less.

2. 2. The method for producing recycled titanium oxide according to claim 1, wherein washing with an acid is carried out before or after the superheated steam treatment.

3. 3. The method for producing recycled titanium oxide according to claim 1, wherein the titanium oxide is pulverized after the superheated steam treatment.

Citation Information

Patent Citations

  • Method and apparatus for cyclic utilization of fluoride in production of titanium-containing compound

    CN103818955A

  • Method for recovering titanium oxide in titanium oxide- containing plastic

    JP2001253713A

  • Method for recycling nylon 6 product

    JP2009227960A

  • Aqueous white dispersion for inkjet ink, inkjet ink, and printed matter

    JP2021105087A

  • Method for recovering titanium dioxide

    JP4628721B2